Patients' perceptions of transrectal prostate biopsy: a qualitative study. - Chapple, A; Ziebland, S; Brewster, S; McPherson, A (2007)
This study explored men's experiences of transrectal prostate biopsy. Fifty men who had had a prostate biopsy talked about the experience as part of an in-depth interview; 36 were interviewed in 2000 about all aspects of prostate cancer, and 14 in 2005 about their experience of prostate-specific antigen testing, subsequent investigations and treatment. Men were recruited via urologists, general practitioners and support groups. In both studies, we aimed to include men of various ages, from different backgrounds, who lived, and had been investigated and treated, in different parts of the UK. A qualitative interpretive approach was taken, combining thematic analysis with constant comparison. Most men described the procedure as merely 'uncomfortable', but some found it stressful, exhausting and extremely painful. Worries included the fear that cancer cells might pass from a man to his wife during ejaculation, and that a biopsy might spread cancer cells to other parts of the body. Men should be given detailed information before a biopsy, so that they are well aware of what might happen. They should also be given the opportunity to voice their fears, so that they can be reassured, and offered some form of pain relief.